The impacts of tobacco control legislation on public view of e-cigarette usage in Macao—The co-word analysis of Macao daily - Chan, Kin-Sun; Xu, Jing; Zhang, Rui; Pang, Patrick Cheong-Iao; Chen, Yu; Zhang, Heng; Liu, Shiyu; Mao, Aimei; Pu, Guanwen; Au, Johnny Ka fai (Frontiers in Communication, 2023)
Macao has been certified as a “Healthy City” by the World Health Organization, and has been adhering to the principle of combining prevention with proper medical care to build its medical system. As tobacco epidemic is a risk factor leading to a series of non-communicable diseases, the Macao SAR Government has continuously improved tobacco control measures. Under the research background, this article takes the news report about “e-cigarette” in Macao Daily as the data source, and understands the development of tobacco control legislation against e-cigarette through co-word analysis and thematic analysis. According to the results of the study and implementation situation, the stages of the legislation against e-cigarette could be divided into three stages, namely the stage before implementation (the first stage), the early stage of implementation (the second stage) and epidemic period (the third stage), and the attention of “teenagers” and “students” has obviously increased. Especially in thematic analysis, e-cigarettes are more likely to lead to drug and smuggling problems. Based on the results of this study, it is suggested that the Macao SAR Government should focus on strengthening the development of adolescents’ healthy behaviors in the control of e-cigarettes, and consider further turning to regional cooperation to promote the “Healthy Bay Area”. Social media and data management are effective means.